Organizational-Economic Model of Coordination of Economic Interests of Subjects of the National System of Social Insurance ("Journal "U". Economy. Management. Finance.", 2017)
As shown by the analysis of experience of advanced Western countries, the institutions responsible for the implementation of the social insurance system can not operate according to the principles of altruism. The emerging transformation in the field of ecology, health, human psychology, and dynamics of macroeconomic indicators show the need to optimize the state of the burden of costs associated with social protection and security. In this regard, became up to date questions of creation of the appropriate organizational-economic model of coordination of economic interests of subjects of the national system of social insurance.
Keywords: social insurance; economic interests of the subjects of the social insurance system; organizational-economic model